По следам пиратов Боденского озера: перевод с немецкого - Брецина Томас (Кникербокер-банда, 1992)
Экземпляры: ф.3 (1995) / Инвентарный номер: 38466 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: Б 87 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-44